Dietary sodium intake level of instant noodle consumers in China - ZHANG Tongwei; CUI Yufeng; MAO Weifeng; ZHAO Fanglei; PAN Feng; LIU Haoyu; LI Jianwen (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveTo assess the impact of reducing sodium content in instant noodles on sodium intake levels among instant noodle consumers under different scenarios， the dietary sodium intake level of instant noodle consumers in China was analyzed.MethodsData were collected from the special monitoring of sodium content in instant noodles and other foods. According to the consumption data of various foods from China Food Consumption Survey from 2017 to 2020， the simple distribution model was used to evaluate the daily dietary sodium intake and distribution of instant noodle consumers， and the contribution rate of different foods. Four scenarios were to reduce the sodium content of instant noodles by 10% or 20%， and 1/2 or 1/3 instant noodles seasoning bag.ResultsThe average sodium content in instant noodle samples was 2 129.30 mg/100 g， and the average dietary sodium intake of instant noodle consumers was 5 462.68 mg/d. The average dietary sodium intake of all age groups was more than 2 000 mg/d （WHO）， and the average dietary sodium intake of 98.53% instant noodle consumers exceeded the proposed intakes for preventing non-communicable chronic diseases value of the corresponding age group. Condiments were the main source of dietary sodium intake of instant noodles consumers， and the contribution of instant noodles was about 12.69%. 1/3 instant noodles seasoning bags could reduce the total sodium intake of instant noodle consumers by 6.74%.ConclusionThe sodium intake level of instant noodles consumers in China was still at a high level. By reducing the sodium content of instant noodles or reducing the amount of condiment package， the sodium intake level of the population could be reduced to a certain degree. This study provided scientific results reference for the domestic instant noodle industry to reduce salt （sodium）.